2011
DOI: 10.1371/journal.pone.0017132
|View full text |Cite
|
Sign up to set email alerts
|

Newly Engineered Magnetic Erythrocytes for Sustained and Targeted Delivery of Anti-Cancer Therapeutic Compounds

Abstract: Cytotoxic chemotherapy of cancer is limited by serious, sometimes life-threatening, side effects that arise from toxicities to sensitive normal cells because the therapies are not selective for malignant cells. So how can they be selectively improved? Alternative pharmaceutical formulations of anti-cancer agents have been investigated in order to improve conventional chemotherapy treatment. These formulations are associated with problems like severe toxic side effects on healthy organs, drug resistance and lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 36 publications
2
29
0
Order By: Relevance
“…One strategy to improve tissue specificity is to encapsulate the drug into a drug-delivery system capable of directing therapeutic compounds to a target site. 25 Increases in drug concentration and drug-residence time in the target area will greatly decrease drug toxicity in nontarget organs and further improve the effectiveness of the drug. rhIFNα 2 b is a good anticancer cytokine, especially for solid tumors, such as HCC.…”
Section: Discussionmentioning
confidence: 99%
“…One strategy to improve tissue specificity is to encapsulate the drug into a drug-delivery system capable of directing therapeutic compounds to a target site. 25 Increases in drug concentration and drug-residence time in the target area will greatly decrease drug toxicity in nontarget organs and further improve the effectiveness of the drug. rhIFNα 2 b is a good anticancer cytokine, especially for solid tumors, such as HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, cancer cell-specifi c siRNAs have been delivered using a modifi ed virosome system on which affi body molecules of HER2 (human epidermal growth factor receptor 2, o en expressed on breast and ovarian cells) were displayed (79). Magnetic force can also be used to drive virosome-formulated anti-cancer medicines into tumor tissues (80). A novel formulation of Decitabine, based on the use of the erythro-magneto-hemagglutinin virosomes (EMHVs) drug delivery system has been refi ned by Cinti's team (63).…”
Section: Virosomes As Carriers For Other Bioactive Molecules In Cancementioning
confidence: 99%
“…81 This new erythrocyte-based DDS has the potential for magnetic-controlled site-specific localization and highly efficient fusion capability with the targeted cells. They showed that the erythro-magneto-HA virosomes DDS is able to attach and fuse with the target cells and to efficiently release therapeutic compounds inside the cells.…”
Section: Cell-based Targeted Drug Delivery Systems For Geriatricsmentioning
confidence: 99%